Effects of Experimental Hyperthyroidism on Collagen IV and Laminin-Î±5 Gene Expression in Balb/C Mouse Seminiferous Tubules: - Sadeghi, Saeed; Jalali, Mahdi; Nikravesh, Mohammad Reza; Sankian, Mojtaba (Galen Medical Journal, 2019)
Background: Hyperthyroidism is one of the disorders of the thyroid gland, an organ that controls the cellular and molecular behaviors of the seminiferous tubule basement membrane (BM), and ultimately, influences its evolutionary process. We aimed to investigate the effects of hyperthyroidism on immunohistochemical characteristics and gene expression levels of collagen IV and laminin-Î±5 in seminiferous tubules BM of Balb/C mice. Materials and Methods: Twenty male Balb/C mice were divided into experimental and control groups. The experimental group received 500 mg/l of levothyroxine (L-thyroxine) diluted in drinking water for two months to inducing hyperthyroidism, which was confirmed by radioimmunoassay. At the end of the study, the mice were sacrificed, and their testes were extracted for immunohistochemistry and real-time polymerase chain reaction assays. Results: Although a weak reaction was observed in the experimental specimens, no significant enhancement was noted in color intensity of type IV collagen in the seminiferous tubules BM of the experimental group as compared to the control group (P>0.05). Collagen IV gene expression results in the experimental group were not significantly different from the controls (P>0.05). Thus, there was a significant increase in laminin Î±5 gene expression compared to the control group (P=0.016). Conclusion: Considering the key role of collagen IV and laminin-Î±5 in the seminiferous tubule BM in the testes, the results of this study indicated that hyperthyroidism has important effects on both structures and functions of these two components. [GMJ.2019;8:e1369]